Mikropoulus, T.A., Pantelidis, V.S., & Chen, C.J. (Eds.). (2009). Virtual Reality in Education [Special Issue]. Themes in Science and Technology Education. Greece: Klidarithmos [ISSN: 1791-3721]. - Tassos, Mikropoulos; Veronica, S. Pantelidis; Chwen, Jen Chen (Themes in Science and Technology Education, 2009)
This article elaborates on how the technical capabilities of virtual reality support the constructivistlearning principles. It introduces VRID, a model for instructional design and developmentthat offers explicit guidance on how to produce an educational virtual environment. Thedefine phase of VRID consists of three main tasks: forming a participatory team, analyzing theappropriateness of employing virtual reality technology to tackle a known learning problem,and performing a feasibility study. The design phase of VRID comprises the macro-strategythat provides guidance on the selection, sequencing, and organization of the subject-mattertopics that are to be presented, and the micro-strategy that provides strategies for effectivepresentation of the learning contents. The development phase includes all the necessary tasksto implement the outcome of the design phase. Among the tasks for this development phaseinclude determining the developmental platform, developing the various components of theeducational virtual environment, performing specialist evaluation as well as conducting oneto-one learner evaluation. Conducting a small group evaluation and performing an effectivenessevaluation study are the two important tasks of the evaluation phase.